Carbon tariffs for financing clean development - Springmann, M (2013)
In order to address carbon leakage and preserve the competitiveness of domestic industries, some industrialized Annex I countries have proposed to implement carbon tariffs. These tariffs would be levied on energy-intensive imports from developing non-Annex I countries that have not agreed to binding emissions reductions. This action could have detrimental welfare impacts, especially on those developing countries, and may not lead to significant reductions in leakage. A recent proposal is to use the revenues generated from carbon tariffs to finance clean development in the relevant exporting non-Annex I countries. This proposal is evaluated using an energy-economic model of the global economy. The model is supplemented by marginal abatement cost curves and bottom-up information on abatement potentials in order to represent how clean development financing affects emissions reductions. The results indicate that carbon tariffs could raise US$3.5-24.5 billion (with a central value of $9.8 billion) for clean development financing. This could reduce the emissions of non-Annex I countries by 5-15% and still leave funds available for other purposes, such as adaptation. Furthermore, recycling the revenues generated from carbon tariffs back to the exporting country itself could alleviate some of the negative welfare impacts associated with them. However, a net negative impact especially on the welfare and gross domestic product of developing countries would remain. © 2013 Copyright Taylor and Francis Group, LLC.